Diagnostic accuracy of R‐wave detection by insertable cardiac monitors. Issue 5 (2nd May 2020) - De Coster, Margot; Demolder, Anthony; De Meyer, Veerle; Vandenbulcke, Filiep; Van Heuverswyn, Frederic; De Pooter, Jan
Abstract: Background: Insertable cardiac monitors (ICM) allow prolonged rhythm monitoring, but the diagnostic performance can be hampered by false positive arrhythmia alerts related to inadequate R‐wave sensing. This study assesses the prevalence and predictors of inadequate R‐wave sensing (both over‐ and undersensing) among different ICM types. Methods: Patients implanted with an ICM at Ghent University Hospital between January 2017 and August 2018 were included. ICM tracings recorded at interrogation or transmitted by remote monitoring were reviewed for inadequate R‐wave sensing leading to false arrhythmia alerts. Patient and implant characteristics were retrieved from the medical records and implant reports. Results: The study screened 135 patients (age 59 ± 19 years, 44% female) implanted with different ICM types: Reveal LINQ™ and XT (Medtronic): n  = 92 (68%), Confirm and Confirm Rx (Abbott): n  = 35 (26%), and BioMonitor 2 (Biotronik): n  = 8 (6%). ICM tracings were analyzed in 112 patients (83%). False arrhythmia alerts occurred in 22 (20%) patients, most frequently related to undersensing (77%). False diagnosis of bradycardia or pause was documented in 64%, false high ventricular rates in 14%, and false atrial fibrillation alerts in 22%. Occurrence of R‐wave changes was not related to patient characteristics or implant R‐wave sensing. A trend toward higher number of inadequate R‐wave sensing seems to occur with nonparasternal implant sites ( P  = .074). Conclusions: False arrhythmia alerts due to inadequate R‐wave sensing occurred in 20% of ICM patients independent of implant features and patient characteristics.